Circulating Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Predicts Future Risk of Cardiovascular Events Independently of Established Risk Factors. Issue 13 (29th March 2016) - Leander, Karin; Mälarstig, Anders; van't Hooft, Ferdinand M.; Hyde, Craig; Hellénius, Mai-Lis; Troutt, Jason S.; Konrad, Robert J.; Öhrvik, John; Hamsten, Anders; de Faire, Ulf
Abstract : Background—: The secreted protein proprotein convertase subtilisin/kexin type 9 (PCSK9) is a promising new target for lowering plasma low-density lipoprotein cholesterol and preventing cardiovascular disease (CVD). The relationship between circulating PCSK9 and incident CVD in the general population is unknown. We investigated whether serum PCSK9 concentration is associated with incident CVD in a prospective cohort study of 4232 men and women 60 years of age at the time of recruitment. Methods and Results—: Incident CVD was recorded by matching to national registries. After 15 years of follow-up, a total of 491 incident events (fatal and nonfatal myocardial infarctions, unstable angina, deaths from coronary heart disease, fatal and nonfatal ischemic strokes) were recorded. Cox proportional hazards model was used to calculate hazard ratios with 95% confidence intervals. Baseline serum PCSK9 concentration predicted incident CVD; concentration in quartile 4 compared with quartile 1 was associated with a hazard ratio of 1.69 (95% confidence interval, 1.30–2.19) after adjustment for sex. Further adjustment for low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, lipoprotein(a), triglycerides, hypertension, diabetes mellitus, smoking, overweight, obesity, physical inactivity, and statin use resulted in a decrease in the hazard ratio to 1.48 (95% confidence interval, 1.12–1.95). Conclusions—: Serum PCSK9 concentration is associated with future risk of CVD even after adjustments for established CVD risk factors. Further studies are needed to confirm this observation.